2019
DOI: 10.1101/582684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-transmission is not the source of newMycobacterium abscessusinfections in a multi-centre cohort of cystic fibrosis patients

Abstract: BackgroundMycobacterium abscessusis an extensively drug resistant pathogen that causes pulmonary disease particularly in cystic fibrosis (CF) patients. Identifying direct patient-to-patient transmission ofM. abscessusis critically important in directing infection control policy for the management of risk in CF patients. A variety of clinical labs have used molecular epidemiology to investigate transmission. However there is still conflicting evidence as to howM. abscessusis acquired and whether cross-transmiss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Our results are in agreement with the previous finding that detection of multiple S. maltophilia strains over time is common (11)(12)(13)(14) and extend previous studies by demonstrating that this pattern may persist for several decades. This pattern of rapid strain acquisition is also consistent with a hypothesis of independent environmental acquisition as the source of new infections in pwCF in CF cohorts with adequate infection control protocols, as has been suggested for other CF pathogens (26,29,32). This is further supported by a lack of epidemiological evidence for infection transmission, and the clonal nature of infecting strains.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results are in agreement with the previous finding that detection of multiple S. maltophilia strains over time is common (11)(12)(13)(14) and extend previous studies by demonstrating that this pattern may persist for several decades. This pattern of rapid strain acquisition is also consistent with a hypothesis of independent environmental acquisition as the source of new infections in pwCF in CF cohorts with adequate infection control protocols, as has been suggested for other CF pathogens (26,29,32). This is further supported by a lack of epidemiological evidence for infection transmission, and the clonal nature of infecting strains.…”
Section: Discussionsupporting
confidence: 87%
“…This latter point is particularly relevant, as many studies have identified a significant proportion of patients with shared strains (as defined by molecular methods). While shared strains as determined through molecular methods may indicate the potential for infection transmission (25,26), it is not sufficient to identify a transmission event (27)(28)(29)(30). This is key, as independent acquisition of the same strain without a CF intermediary is well known to occur with other CF pathogens (26,28,29), confounding our ability to understand infection transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with the previous finding that detection of multiple S. maltophilia strains over time is common (Vidigal et al, 2014;Pompilio et al, 2016;Chung et al, 2017;Esposito et al, 2017) and extend previous studies by demonstrating that this pattern may persist for several decades. This pattern of rapid strain acquisition is also consistent with a hypothesis of independent environmental acquisition as the source of new infections in pwCF in CF cohorts with adequate infection control protocols, as has been suggested for other CF pathogens (Yan et al, 2019;Doyle et al, 2020;Stapleton et al, 2020). This is further supported by a lack of epidemiological evidence for infection transmission, and the clonal nature of intra-pwCF strains.…”
Section: Discussionsupporting
confidence: 87%
“…This latter point is particularly relevant, as many studies have identified a significant proportion of patients with shared strains (as defined by molecular methods). While shared strains as determined through molecular methods may indicate the potential for infection transmission (Stapleton et al, 2020;Gabrielaite et al, 2021), it is not sufficient to identify a transmission event (Parkins et al, 2018;Doyle et al, 2020;Izydorczyk et al, 2020Izydorczyk et al, , 2022. This is key, as independent acquisition of the same strain without a CF intermediary is well known to occur with other CF pathogens (Doyle et al, 2020;Izydorczyk et al, 2020;Stapleton et al, 2020), confounding our ability to understand infection transmission.…”
Section: Discussionmentioning
confidence: 99%